Inhibition of Polyunsaturated Fatty Acids Synthesis Decreases Growth Rate and Membrane Fluidity of Rhodosporidium kratochvilovae at Low Temperature. Issue 8 (28th June 2017) - Wang, Jun; Chen, Wei; Nian, Hongjuan; Ji, Xiuling; Lin, Lianbing; Wei, Yunlin; Zhang, Qi
Abstract: The intention of this study was to investigate the role of polyunsaturated fatty acids (PUFA) in the cold adaptation of Rhodosporidium kratochvilovae YM25235 by knockout of the Δ 12 /Δ 15 ‐fatty acid desaturase gene ( RKD12 ) to inactivate Δ 12 /Δ 15 ‐fatty acid desaturase. Polymerase chain reaction (PCR) amplification was used to detect the genomic structure of RKD12 gene in YM25235. The RKD12 gene was knocked out by DNA homologous recombination to inhibit the biosynthesis of PUFA. Then, the contents of linoleic acid (LNA) and α‐linolenic acid (ALA) after gene knockout were investigated using a gas chromatography‐mass spectrometer, followed by determination of the growth rate and membrane fluidity of YM25235 at low temperature. After PCR amplification, a 1611 bp genomic fragment was amplified from YM25235. When the RKD12 gene was knocked out, the contents of LNA and ALA in YM25235 significantly decreased. The growth rate and membrane fluidity of YM25235 decreased significantly at low temperature. Inhibition of PUFA biosynthesis by RKD12 gene knockout influenced cold adaptation of YM25235 by decreasing the PUFA content in cell membranes and reducing the growth rate and membrane fluidity of YM25235 at low temperature.